2007
DOI: 10.1084/jem.20070247
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 release induced by liver ischemia involves Toll-like receptor 4–dependent reactive oxygen species production and calcium-mediated signaling

Abstract: Ischemic tissues require mechanisms to alert the immune system of impending cell damage. The nuclear protein high-mobility group box 1 (HMGB1) can activate inflammatory pathways when released from ischemic cells. We elucidate the mechanism by which HMGB1, one of the key alarm molecules released during liver ischemia/reperfusion (I/R), is mobilized in response to hypoxia. HMGB1 release from cultured hepatocytes was found to be an active process regulated by reactive oxygen species (ROS). Optimal production of R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
521
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 558 publications
(546 citation statements)
references
References 50 publications
22
521
1
2
Order By: Relevance
“…And it is safe to say that post translational modifications play an important role in the nucleocytoplasmic redistribution. As mentioned above, oxidation, hyperacetylation and phosphorylation of HMGB1 contribute to its cytoplasmic relocation in inflammatory and cancer cells (Hoppe et al, 2006;Youn et al, 2006;Tsung et al, 2007;Kang et al, 2009;Evankovich et al, 2010;Lee et al, 2012). Experiments in Schistosoma mansoni conclusively demonstrated that acetylation and phosphorylation played roles in cellular trafficking, culminating with its secretion to the extracellular milieu de Abreu da Silva et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…And it is safe to say that post translational modifications play an important role in the nucleocytoplasmic redistribution. As mentioned above, oxidation, hyperacetylation and phosphorylation of HMGB1 contribute to its cytoplasmic relocation in inflammatory and cancer cells (Hoppe et al, 2006;Youn et al, 2006;Tsung et al, 2007;Kang et al, 2009;Evankovich et al, 2010;Lee et al, 2012). Experiments in Schistosoma mansoni conclusively demonstrated that acetylation and phosphorylation played roles in cellular trafficking, culminating with its secretion to the extracellular milieu de Abreu da Silva et al, 2011).…”
Section: Discussionmentioning
confidence: 92%
“…Another study reported that the conformation of Cys106, whether reduced or oxidated, was critical for regulating nucleocytoplasmic shuttling of HMGB1 (Hoppe et al, 2006). In cultured hepatocytes, HMGB1releasing was regulated by TLR4, which dependened on reactive oxygen species production (Tsung et al, 2007). Later, it has been demonstrated that decreased histone deacetylases(HDACs) activity in hepatocytes, following ischemia and reperfusion, was a mechanism that promoted hyperacetylation and secretion of HMGB1 (Evankovich et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…17 Through the TLR4 system, HMGB1 produces an early inflammatory response, 17 leading to amplification of HMGB1 secretion. 27 Active HMGB1 secretion from phagocytes displays delayed kinetics. 3,9,20 In experimental models of endotoxemia, HMGB1 levels increase 12 to 18 hours after peak TNF-␣ levels.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Interestingly, HMGB1 was reported to rapidly mobilize and release into system circulation from damaged liver in the setting of liver I/R injury. 34,35 Previous studies also demonstrated that serum HMGB1 level remained elevated until 12 h after reperfusion, and that the removal of excessive serum HMGB1 with adsorption column improved the lung injury score. 28 Whether or not HMGB1 was transported to the lung and whether downstream signaling pathways in lung were activated was not investigated.…”
Section: Discussionmentioning
confidence: 99%